EMPLOYEE PERFORMANCE: A PERSPECTIVE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Said Almaududi (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
The purpose of this research is 1. To know the description OCB and Employee performance at CV. Jaya Indah Motor Jambi City. 2. To know the influence of OCB on employee performance on the CV. Jaya Indah Motor Jambi. The Method of this research is descriptive and quantitative analysis. The population in this research is the employees of CV. Jaya Indah Motor Jambi. Withdrawal of samples conducted in stratified random sampling. The total sample in this research is as much as 50 respondents. This research analyzes the influence of the independent variable X (OCB) to dependent variable Y (employee performance), can be described in a simple regression model. OCB on the CV. Jaya Indah Motor Jambi City is on high criteria with an average score of 141.4. Furthermore, the performance on the CV. Jaya Indah Motor Jambi City is in the medium criteria with an average score of 137.5. Based on the hypothesis test it is known that there is significant influence between OCB on employee performance on the CV. Jaya Indah Motor Jambi City